1988
DOI: 10.1101/sqb.1988.053.01.115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrovasodilators, Endothelium-dependent Vasodilators, and Atrial Peptides on cGMP

Abstract: The interactions of the nitrovasodilators, endothelium-dependent vasodilators, and atrial peptides with cGMP synthesis have proved to be useful and important leads to the functions of cGMP and signal transduction mechanisms. Although considerable progress has been made, many important questions remain to be answered. Nevertheless, the guanylate cyclase-cGMP system clearly represents an important second-messenger system that mediates the effects of numerous agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…37 Peroxynitrite has been shown to interact with proteins and produce nitrotyrosine residues. 15 Through the use of a nitrotyrosine antibody, we are able to clearly show that CsA treatment significantly increases the amount of nitrotyrosine (see Figure 7). Our data also show that the formation of nitrotyrosine is inhibited by the addition of the NADPH oxidase inhibitor DPI, the antioxidant NAC, as well as the oxygen radical scavenger Tiron and the peroxynitrite scavenger uric acid.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…37 Peroxynitrite has been shown to interact with proteins and produce nitrotyrosine residues. 15 Through the use of a nitrotyrosine antibody, we are able to clearly show that CsA treatment significantly increases the amount of nitrotyrosine (see Figure 7). Our data also show that the formation of nitrotyrosine is inhibited by the addition of the NADPH oxidase inhibitor DPI, the antioxidant NAC, as well as the oxygen radical scavenger Tiron and the peroxynitrite scavenger uric acid.…”
Section: Discussionmentioning
confidence: 87%
“…NO has such a high affinity for the superoxide anion that it has been shown to compete with SOD for binding of O 2 Ϫ . 15 It has even recently been shown that CsA treatment can induce the formation of peroxynitrite, dependent on the concentration of superoxide anion. 37 Peroxynitrite has been shown to interact with proteins and produce nitrotyrosine residues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both within the same cell and in specific target cells, this NO-like factor (or group offactors) activates soluble guanylyl cyclase, thereby acting as an intra-and intercellular signal molecule to regulate the intracellular concentration of cGMP (11)(12)(13)(14). Earlier studies have demonstrated that L-arginine could activate guanylyl cyclase in brain and neuronal cells (15, 16); however, the mechanisms were not elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of GAF from L-arginine is catalyzed by an NADPH-dependent GAF synthase (6,(21)(22)(23)(24)(25). GAF synthase and its target enzyme, soluble guanylyl cyclase, represent the protein components of this signal-transduction pathway (13,14,17,18,26,27). In rat cerebellum, GAF synthase activity is due to a cytosolic Ca2+/calmodulin-regulated isoform of the enzyme.…”
mentioning
confidence: 99%